Health and Animal Agriculture in Developing Countries - Zilberman, David; Otte, Joachim; Roland-Holst, David; Pfeiffer, Dirk.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
This book provides an overview of the state of animal agriculture and present methodologies and proposals to develop policies that result in sustainable and profitable animal production that will protect human and environmental health, enhance livelihood of smallholders and meet consumer needs. The book combines lessons of the past, factual foundation to understand the present, analytical tools to design and improve policies, case studies that provide both empirical grounding and applications of some of the strategies suggested in this book, and finally, a proposal for the way forward. The book is divided into five parts. The first section of the book will provide an analysis of the evolution of animal agriculture in the context of the development of farming systems over the years. The second part of the book will provide an overview of some of the major strands of literature on the economics and health of animal agriculture. The third and fourth sections of the book emphasize an important case study, avian influenza with applications in Southeast Asia and Africa. Finally, the book summarizes the state of knowledge and current trajectory of animal agriculture and provides policy recommendations to both control animal disease and support research that would lead to prosperous, sustainable animal agriculture in the future. This volume contains contributions from leading researchers in agricultural economics environmental economics, veterinary science, and natural resource management and will be of interest to academics and students in those fields as well as policy-makers in government or international organizations that focus on animal agriculture, health and the environment.
Introduction -- Evolution of Animal Agriculture -- The History of Animal Disease: The Control of BTbH -- Economics of Contract Farming and Supply Chain -- Livestock and Livelihood: A Global Perspective -- Policy Challenges of Controlling Animal Disease -- Livestock and Livelihood: A Portfolio Approach -- Animal Disease and Industrialization of Agriculture -- Economics of Controlling Externalities of Animal Disease -- Dynamic Perspective on Control of Animal Disease -- Public Investment in Controlling Public Health Risks from Livestock -- Developing Alternative Solutions to Controlling Highly Pathogenic Animal Diseases -- Consumer Meat Demand: Role of Preferences and Social Norms -- Epidemiology of Avian Influenza -- Spread of Avian Influenza -- Control and Surveillance of Avian Influenza -- Epidemiological and Economical Implications of Vaccination for Avian Influenza -- Integrating Epidemiology and Economics -- Modeling Alternative On-Farm Solution -- Controlling Animal Disease in Africa -- Poultry Sector Transition in Cambodia -- Supply Chain Solutions to Animal Safety Problems -- Contracting as a Mechanism for Avian Flu Risk Management and Poverty Reduction -- Micro-Contracting and Smallholder Livestock Supply Chain -- Conclusion.
Keywords: Economics; Environmental management; Development Economics; Farm economics; Environmental economics; Economics/Management Science; Agricultural Economics; Development Economics; Environmental Economics; Environmental Management